Gendering covid-19: The role of women in strengthening the family economy - Inayatillah, Inayatillah; Mellyan, Mellyan (Universitas Islam Negeri Ar-Raniry, 2022)
ABSTRAKIn addition to bringing changes in every sector of life, the Covid-19 pandemic is a challenge for women. In difficult conditions, women turned out to have a role in strengthening the economy in the midst of the Corona Virus Disease-19 (Covid-19). The formulation of the problem from this research was how women manage to survive and contribute to the family's economic well-being. The study employed descriptive analytic qualitative research approaches. The data collection method was conducting interviews with women parking in Meulaboh, West Aceh, and combining them with their personal histories. This study also employed observations or monitors and gathered information from online journals, books, newspapers, and other sources. According to research, even when women's income was low, they still tried to work to make ends meet despite the covid-19. During the epidemic, the majority of respondents reported their income had decreased. Only for those who work at Pasar Bina Usaha, which is unsurprising given that the market was where the inhabitants of West Aceh get their most basic requirements met. They also wanted the government to assist them and pay attention to them while they faced difficult circumstances. Government policies, the commercial sector, academics, and the community must all work together to raise awareness of economically vulnerable women during the epidemic, to provide more gender-responsive support, and to involve women in decision-making.Keywords: The role of women, covid-19, the family economy